PROSEDUR PENGUJIAN SUBSTANTIF ATAS AKUN ASET TETAP PT. XYZ OLEH KAP BHARATA, ARIFIN, MUMAJAD & SAYUTI - Astrid Diva Az-zahra (2023)
Audit procedures are a series of tests on account balances in financial reporting which are used as a reference for testing conformity and providing an opinion if financial reporting has been reported fairly. Fixed assets are objects with a form that an agency has to support the operational activities of an agency. This report aims to describe the results of the audit of fixed asset accounts at PT. XYZ carried out by KAP BAMS. The subject matter chosen in this study is a procedural audit of fixed assets. This discussion was chosen because the audit of fixed assets is an example of the most important aspects, especially when presenting balances in an agency's financial reporting. Meanwhile, procedural audits are carried out in a structured way from audit engagements, audit planning to audit implementation and reporting. Based on the results of substantive testing of fixed asset account audits, it can be concluded that KAP BAMS has carried out in accordance with applicable regulations and the auditors did not find any misstatements or disclosures on the balance of fixed assets of PT. XYZ.